The Synergy of Pedagogical Environment and Psychological Climate in Fostering Creative Self-Realization of Students in Music Education - Jianghua Li; N. Asipova; Zheng, Qianwen; Zaichao Zhai; Wenhui Dong (Environment and Social Psychology, 2025)
Chinese music classrooms face large classes, uneven resources, and time-limited lessons. We tested whether a compact “Blueprint” (autonomy-supportive tasks, transparent assessment, flow-aligned deep-work windows, weekly low-stakes improvisation, structured collaboration, inclusive repertoire) improves Psychological Climate (PC) and, through it, Creative Self-Realization (CSR). Cluster-randomized, mixed-methods trial in ordinary schools: 24 classes (12 Blueprint; 12 BAU), ≈38 students/class (N ≈ 900). Measures at baseline (T0), midline (T1), post (T2), and short follow-up (T3). Multilevel regressions and multilevel SEM tested PE → PC → CSR; blinded external ratings scored creative products (0–4 rubric). Blueprint improved the higher-order PC factor at T2 (β = 0.33, 95% CI [0.22, 0.44], p < .001). PC strongly predicted CSR (β = 0.52, [0.43, 0.60], p < .001); the indirect Blueprint → CSR effect via PC was β = 0.17 ([0.10, 0.25], p < .001), total β = 0.26 ([0.16, 0.36], p < .001). PC subscale effects (Cohen’s d) at T2: Safety 0.37, Autonomy 0.35, Competence 0.31, Goal clarity 0.29, Belonging 0.27. Product gains at T2 (Blueprint − BAU, 0–4 scale): Originality +0.38, Coherence +0.32, Craft +0.28, Reflective Intent +0.35. Lever models: assessment support → PC-Competence β = 0.28 and PC-Safety β = 0.26; flow design → PC-Goal clarity β = 0.24 with small direct boosts to Originality (β = 0.11) and Coherence (β = 0.09); improvisation dosage (per +5 min/week) → CSR β = 0.06. Moderation: PC × cultural inclusivity β = 0.07 (simple slopes: 0.58 vs 0.46), stronger Blueprint effects for lower-skill learners (INT→PC 0.41 vs 0.24), and buffering in large/low-resource classes via peer roles and stations. Same-lesson feedback improved next-iteration quality by +0.12. Mean fidelity ≈ 78%. Feasible, routine-based design warms climate and unlocks creativity in typical Chinese music classrooms. Small architectural shifts—clear criteria, protected deep-work, frequent improv, structured collaboration, inclusive repertoire, and same-lesson feedback—produce measurable gains in student engagement, efficacy, identity, and creative products.